2021
DOI: 10.1101/2021.03.25.21254322
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of monoclonal antibody treatment on hospitalization and mortality among non-hospitalized adults with SARS-CoV-2 infection

Abstract: Background: Monoclonal antibody (mAb) treatment may prevent complications of COVID-19. We sought to quantify the impact of bamlanivimab monotherapy on hospitalizations and mortality, as well as Emergency Department (ED) visits without hospitalization, among outpatients at high risk of COVID-19 complications. Methods: We compared patients receiving mAb to patients who met criteria but did not receive mAb from December 2020 through March 2021. The study population selection used propensity scores to match 1:1 b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 16 publications
5
28
1
Order By: Relevance
“…As prior studies have suggested that patients with medical comorbidities are at higher risk of severe and critical illness, early treatment with bamlanivimab may have mitigated this progression. (11,18,19) Due to the evolution of SARS-CoV-2 variants, bamlanivimab is no longer authorized for use as monotherapy. Despite this, the results of this study which showed the real-world efficacy of bamlanivimab monotherapy in the prevention of hospital admission and other serious clinical outcomes, provides the proof of concept that treatment with neutralizing antibodies is an effective strategy to mitigate the current COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As prior studies have suggested that patients with medical comorbidities are at higher risk of severe and critical illness, early treatment with bamlanivimab may have mitigated this progression. (11,18,19) Due to the evolution of SARS-CoV-2 variants, bamlanivimab is no longer authorized for use as monotherapy. Despite this, the results of this study which showed the real-world efficacy of bamlanivimab monotherapy in the prevention of hospital admission and other serious clinical outcomes, provides the proof of concept that treatment with neutralizing antibodies is an effective strategy to mitigate the current COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…(8)(9)(10) Upon the issuance of the EUA, institutions across the US established infusion facilities for the administration of monoclonal antibodies. (11)(12)(13)(14) The Mayo Clinic developed its dedicated infusion facilities and assembled multidisciplinary teams to coordinate monoclonal antibody infusions to patients with coronavirus disease-19 (COVID- 19) who are eligible under the EUA. (7,15) This study was conducted to analyze the association of bamlanivimab monotherapy with clinical outcomes in high-risk patients with mild to moderate COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…In an early matched study on 468 patients by Bariola et al, patients receiving bamlanivimab were less likely to experience hospitalization or mortality (OR 0.31) and hospitalization or emergency department visit without hospitalization (OR 0.50). The impact of bamlanivimab was more pronounced in prevention of hospitalization (among all age groups, OR 0.35) than mortality or emergency department visit without hospitalization, and most strongly associated with patients age 65 years and older (primary outcome OR 0.28) [ 55 ].…”
Section: Post-launchmentioning
confidence: 99%
“…In November 2020, the Food and Drug Administration issued emergency use authorizations for monoclonal antibody (mAb) monotherapy bamlanivimab and combination therapy casirivimab/imdevimab to treat COVID-19 among individuals at high risk for progressing to severe disease [5]. These mAb treatments were shown to be effective for preventing progression of disease and COVID-19-associated hospitalizations [6,7]. Given that a significant number of individuals remain at risk for COVID-19 in the U.S. [8], mAb treatments will continue to be critical for saving lives and reducing COVID-19 morbidity and mortality [9,10].…”
Section: Background and Significancementioning
confidence: 99%